2018
DOI: 10.1029/2018jf004718
|View full text |Cite
|
Sign up to set email alerts
|

Growing Forced Bars Determine Nonideal Estuary Planform

Abstract: The planform of estuaries is often described with an ideal shape, which exponentially converges in landward direction. We show how growing topographically forced nonmigratory (i.e., anchored) bars determine the large‐scale estuary planform, which explains the deviations observed in the planform of natural estuaries filled with bars compared to the ideal planform. Experiments were conducted in a 20‐m long, 3‐m‐wide tilting flume, the Metronome. From a narrow, converging channel a self‐formed estuary developed c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(119 citation statements)
references
References 75 publications
8
109
2
Order By: Relevance
“…In this paper we will present an experiment with only sand, an experiment with a low mud supply and an experiment with a high mud supply. The experiment with only sand is also presented in Leuven et al (2018a), where estuaries with growing forced tidal bars are shown to determine a non-ideal estuary planform, which serves as a reference experiment for this study. The experiments are conducted in a recently built flumethe Metronome -of 20 3 m in size, which drives tidal flow by periodic tilting of the entire flume ( Figure 1; Kleinhans et al, 2017b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we will present an experiment with only sand, an experiment with a low mud supply and an experiment with a high mud supply. The experiment with only sand is also presented in Leuven et al (2018a), where estuaries with growing forced tidal bars are shown to determine a non-ideal estuary planform, which serves as a reference experiment for this study. The experiments are conducted in a recently built flumethe Metronome -of 20 3 m in size, which drives tidal flow by periodic tilting of the entire flume ( Figure 1; Kleinhans et al, 2017b).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we solved a classic scaling conflict between sediment friction and sediment mobility by using a coarse sediment to prevent hydraulic smooth conditions and associated scour holes (Kleinhans et al, 2017a), and at the same time increasing the Shields mobility number to similar values to those found in nature by driving the periodic flow by periodic flume tilting 2017b, as explained in detail below. Pilot set-ups of this system have already been used in studies on tidal basins and ebb-and flood-dominant channels (Kleinhans et al, 2012(Kleinhans et al, , 2014b(Kleinhans et al, , 2015, and the Metronome has also already been proven to be a more effective method of producing dynamic estuaries compared to solely vertical water fluctuations (Kleinhans et al, 2017b;Leuven et al, 2018a). Previous morphodynamic experiments showed that tidal bars scale similarly to tidal bars in natural systems: the length-to-width ratio and their correlation with local estuary width is in accordance with natural systems (Leuven et al, 2018a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…funnel-shaped tidal channels, tidal mouth bars, etc.) Physical experiments can help bridge this knowledge gap, allowing one to capture delta evolution at a spatial and temporal resolution otherwise impractical in the field (Malverti et al, 2008;Paola et al, 2009;Kleinhans et al, 2012Kleinhans et al, , 2014aStefanon et al, 2012;Braat et al, 2018;Lentsch et al, 2018;Leuven et al, 2018). Physical experiments can help bridge this knowledge gap, allowing one to capture delta evolution at a spatial and temporal resolution otherwise impractical in the field (Malverti et al, 2008;Paola et al, 2009;Kleinhans et al, 2012Kleinhans et al, , 2014aStefanon et al, 2012;Braat et al, 2018;Lentsch et al, 2018;Leuven et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For rivers and estuaries these include salt marshes with, for example, Spartina species, mangrove forests including Avicennia species, riparian forests with, for example, Salicacea species and vegetated deltas with Nelumbo species. Figure 1 is an illustration of the biogeomorphological patterns that emerge when different vegetation species are combined in tidal experiments (Kleinhans et al, 2017a;Braat et al, 2018;Leuven et al, 2018) with scaling, sediment and vegetation treatment similar to that in van Dijk et al, (2013). The ecoengineering species in these environments have starkly different settling conditions, inundation and uprooting tolerance, rooting density and added bank strength and flow to higher bathymetry flow focusing/retardation (Corenblit et al, 2007) Saltmarsh Mean water level Soil enforcement Spartina, Juncus up to high tide substantial flow retardation (Schwarz et al, 2018) Freshwater floodplain Adjacent to channel Marsh-like effects for grasses; Phragmites, Typha up to highest flooded areas riparian type effects for trees resistance.…”
Section: Introductionmentioning
confidence: 99%